Histomorphometric characteristics of immune cells in small intestine of pigs perorally immunized with vaccine candidate F18ac+ nonenterotoxigenic E. coli strain - I. Valpotic (European Journal of Histochemistry, 2009)
Colidiarrhea and colienterotoxemia caused by F4+ and/or F18+ enterotoxigenic E. coli (ETEC) strains are the most prevalent infections of suckling and weaned pigs. Here we tested the immunogenicity and protective effectiveness of attenuated F18ac+ non-ETEC vaccine candidate strain against challenge infection with F4ac+ ETEC strain by quantitative phenotypic analysis of small intestinal leukocyte subsets in weaned pigs. We also evaluated levamisole as an immune response modifier (IRM) and its adjuvanticity when given in the combination with the experimental vaccine. The pigs were parenterally immunized with either levamisole (at days -2, -1 and 0) or with levamisole and perorally given F18ac+ non-ETEC strain (at day 0), and challenged with F4ac+ ETEC strain 7 days later. At day 13 the pigs were euthanatized and sampled for immunohistological/histomorphometrical analyses. Lymphoid CD3+, CD45RA+, CD45RC+, CD21+, IgA+ and myeloid SWC3+ cell subsets were identified in jejunal and ileal epithelium, lamina propria and Peyer’s patches using the avidin-biotin complex method, and their numbers were determined by computer-assisted histomorphometry. Quantitative immunophenotypic analyses showed that levamisole treated pigs had highly increased numbers of jejunal CD3+, CD45RC+ and SWC3+ cells (p<0.05) as compared to those recorded in nontreated control pigs. In the ileum of these pigs we have recorded that only CD21+ cells were significantly increased (p<0.01). The pigs that were treated with levamisole adjuvanted experimental vaccine had significantly increased numbers of all tested cell subsets in both segments of the small intestine. It was concluded that levamisole adjuvanted F18ac+ non-ETEC vaccine was a requirement for the elicitation of protective gut immunity in this model; nonspecific immunization with levamisole was less effective, but confirmed its potential as an IRM.